OP0042 Do We Know How and When to Stop Immunosuppressants in Lupus Patients?. (10th June 2014) - Touma, Z.; Gladman, D.D.; Ibanez, D.; Urowitz, M.B.
Abstract : Background: After achieving low disease activity/remission, immunosuppressant (IS) therapy might be stopped, but information on whether and how this should be done is limited. Objectives: To determine if stopping IS in patients in remission is possible without triggering flare. Methods: Analysis was conducted on all patients seen in The Lupus Clinic in whom IS was tapered and stopped. Inclusion criteria: 1) in clinical remission (no activity in the clinical SLEDAI-2K descriptors and absence of proteinuria or lupus related thrombocytopenia and leukopenia) and 2) prednisone ≤7.5mg/day. Three time points are identified in each patient: 1) Tapering start - defined as the first visit with a decrease of at least 25% in the dose of IS 2) IS Stop - defined as the day when IS was completely stopped 3) Study end - defined as the date of flare or last clinic visit following IS stop. Study endpoints: Flare - Introduction of new IS or any increase of prednisone dosage in the context of clinically active lupus. Flare was evaluated within the first 2 years from IS stop and also at any time after IS stop. Descriptive statistics were used. Patients who flared within 2 years were compared to those who did not (t-test and χ 2 tests). Kaplan-Meier curve was used to evaluate the time to flare after IS stop. Results: Of the 1678 patients registered at the Lupus Clinic, 973 were ever on IS and 99 stopped IS [56 azathioprine (AZA); 25 methotrexate (MTX), 18 mycophenolate mofetil (MMF)]. At tapering start, mean age was 40.4± 13.1 and mean disease duration was 11.4±9.4 years. The length of time from tapering start to IS stop was 1.5±1.7 years (Median=0.9). Of the 99 patients, 25 flared within 2 years (16 on AZA; 7 on MTX and 2 on MMF; p=0.31). 46 of the patients had follow up available beyond 2 years; 32 were followed beyond 3 years, 26 beyond 4 years and 24 beyond 5 years. 17 patients experienced a flared after year 2. Comparing patients who flared within 2 years to those who did not, the percentage of patients with positive serology at the time of IS stop was greater in those who flared, 68 compared to 41% (Table 1 ). Time from Tapering start to IS stop was 1.8±1.8 years in the no flare group and 0.9±0.9 years in the flare group (p=0.002). Using KM curve for time to flare (Figure 1 ) showed that at 1, 2, 3, 4 and 5 years, the percent of patients who flared was 17%, 30%, 46%, 49% and 51% respectively. Conclusions: Within 2 years, successful stopping of IS is possible in about 70% of clinically stable patients. Half were successful within 3 year and this proportion was stable up to 5 years. Patients who discontinued IS slowly are less likely to flare within 2 years. At the time of IS stop, serologically active patients were more likely to flare on follow-up visits. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5739